Investigating Fishing Vessel Casualties in Peru: A Technical and Scientific Review to Support New Regulations - Mantari, José (2023)
The reporting system for fishing vessel and crew casualties in Peru needs a disruptive change in order to know what the risks in terms of marine safety are, who should manage them, and how they should be managed. According to a technical review on accidents recorded by the Peruvian Direction of Captaincies and Coast Guards (DICAPI), it is evident there is a need to process the available information on casualties of fishing vessels and crew in the fishing industry since this information is not easy to analyze. Nevertheless, this paper provides the casualties reported between Citation: Mantari, J.; Ramirez, J.; Figueroa, E.; Huerta, J.; Cipriano, W.; Amaya, D.; Cuba, L.; Guedes Soares, C. Investigating Fishing Vessel Casualties in Peru: A Technical and Scientific Review to Support New Regulations. J. Mar. Sci. Eng. 2023, 11, 2224. https://doi.org/10.3390/ jmse11122224 Academic Editor: Md Jahir Rizvi Received: 14 August 2023 Revised: 30 October 2023 Accepted: 13 November 2023 Published: 24 November 2023 Copyright: © 2023 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/). 2004 and 2010, and from 2013 to 2020. In order to understand the research endeavors and trends surrounding the safety of fishing vessels, a systematic review using VOSviewer was performed. After a deep analysis and study of the information available in Peru, as well as reports and regulations from the International Maritime Organization (IMO), Food and Agriculture Organization (FAO), International Convention for the Safety of Life at Sea (SOLAS), and the recent advances available in the scientific literature on the safety of fishing vessels and crew casualties around the world, this paper presents some proposals regarding the current Peruvian scenario that are expected to be considered in new regulations